Envisioning new directions in research on individual differences - Weijia Yang; Xuesong (Andy) Gao (Studies in Second Language Learning and Teaching)
In this article, we highlight the important achievements of the editors and contributors in this special issue. We argue that this collection of studies on individual differences (IDs) advances the field in terms of theoretical diversification, methodological improvement, and pedagogical innovation. We also contend that a renewed interest in ID research will enable second language acquisition (SLA) researchers and language educators to show how language education helps language learners acquire desirable attributes and dispositions. In turn, related findings will enable researchers and educators to articulate the value of language learning for the public as many language educators may fear that generative artificial intelligence and translation tools will remove a major motivation for learning languages.